2018
DOI: 10.1109/jetcas.2018.2818185
|View full text |Cite
|
Sign up to set email alerts
|

Motion and Noise Artifact-Resilient Atrial Fibrillation Detection Using a Smartphone

Abstract: We have recently found that our previously-developed atrial fibrillation (AF) detection algorithm for smartphones can give false positives when subjects’ fingers or hands move, as we rely on proper finger placement over the smartphone camera to collect the signal of interest. Specifically, smartphone camera pulsatile signals that are obtained from normal sinus rhythm (NSR) subjects but are corrupted by motion and noise artifacts (MNAs) are frequently detected as AF. AF and motion-corrupted episodes have the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…For example, the thresholds of some features were first used to exclude poor pulses, then an ML model was built for the detection of AF in the clean pulses. 64,65 Table 2 is a chronological summary of the selected ML studies and the reported performance results. All the studies reported in the Table 2 were based in short length of PPG segment, with maxima of 2 min.…”
Section: Ppg Representationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the thresholds of some features were first used to exclude poor pulses, then an ML model was built for the detection of AF in the clean pulses. 64,65 Table 2 is a chronological summary of the selected ML studies and the reported performance results. All the studies reported in the Table 2 were based in short length of PPG segment, with maxima of 2 min.…”
Section: Ppg Representationsmentioning
confidence: 99%
“…This situation can lead sinus rhythm signals corrupted by motion artifacts to be incorrectly detected as AF and vice versa. 65,73 The most common approach to deal with this issue is to simply discard the corrupted segments and use only the clean parts of PPG signals. 49,50,58,60,64,74 Some of the works followed a two-step approach: first, to identify motion artifacts by using accelerometer data, or by performing PPG signal quality assessment; and second, to perform AF detections with only good quality signals.…”
Section: Other Cardiac Arrhythmiasmentioning
confidence: 99%
“…Third, there are many methods for improving smartphone PPG accuracy [27,[29][30][31][32][33]. For example, adding a suitable bandpass filter for signal processing [28] or excluding data with RR intervals that differ more than a certain threshold [70] are simple and effective approaches to reduce noise.…”
Section: Limitationsmentioning
confidence: 99%
“…Given that smartphones with in-built cameras have become a part of modern life, using them to access health information is an ideal alternative when ECGs or similar medical devices are not available [26]. In addition, there have been several reported techniques for increasing the accuracy of smartphone PPG, such as point-of-interest selection [27], bandpass filtering [28], adaptive signal thresholding [29], motion detection techniques [30][31][32], interpolation techniques [33], and signal decomposition methods [34][35][36]. Bioengineering studies indicate that the average HR [37] and HRV measured using smartphone PPG are comparable with those measured using gold standard ECGs [21,28,[38][39][40].Although it is a promising solution for practical data collection and has an accuracy that has been well proved in several experiments, using smartphone PPG to measure HRV has received limited research attention in applied disciplines such as medicine or psychology [41]; a possible explanation is the lack of robustness in practical scenarios.…”
mentioning
confidence: 99%
“…These smartphone methods can be used for heart rate estimation, atrial fibrillation detection, oxygen saturation measurement, and BP estimation [39]- [45]. Two smartphones were used in [42] to record the audio signal and the PPG signal together to estimate BP.…”
Section: Introductionmentioning
confidence: 99%